Costa Rica : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that the economic performance of Costa Rica weakened in 2000. Real GDP growth slowed to 1.7 percent, from more than 8 percent a year in 1998-99, reflecting in part deterioration in terms of trade, the end of the construction phase of a large foreign direct investment project by Intel, and the effect of high real interest rates on domestic demand. Inflation remained at 10 percent during the year. In the structural area, the assembly approved legislation to open up the telecommunications and electricity sectors to private investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet